(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To examine the budget impact of reimbursing Gd-EOB-DTPA for MRI use in diagnosing hepatocellular carcinoma and liver metastatic cancers in Vietnam. Methods: A model-based budget impact analysis was conducted from the payer’s perspective over five years, comparing scenarios with and without 100% reimbursement. Input parameters were obtained from the literature and expert consultations. Results: Full reimbursement would save 2.77 billion VND for hepatocellular carcinoma diagnosis and 17.05 billion VND for liver metastatic cancers diagnosis, mainly owing to reduced treatment costs from earlier and accurate diagnoses. Cost savings were also observed at 30%, 50%, and 70% reimbursement rates. Conclusion: Reimbursing Gd-EOB-DTPA provides significant economic benefits and improves access to high-precision imaging, supporting its inclusion in the health insurance reimbursement list.